Technical aspects of the development of solar energy refrigeration technology on solid sorbents - Y. V. Shipulina; M. F. Rudenko; V. N. Sainova (Вестник Дагестанского государственного технического университета: Технические науки, 2023)
Objective. The purpose of the study is a scientific review of the stages of development of refrigeration technology with sorption action on solid sorbents and an assessment of the current state of development of such household equipment in relation to the use of solar energy.Method. The dynamics of the development of solar energy refrigeration equipment based on sorption thermotransformers, the working vapors of which are solid sorbents and ozone-safe refrigerants, are analyzed. The beginning of development comes from the creation of periodic installations operating from the thermal energy of traditional energy carriers: hot water, burning of hydrocarbon or organic fuels, electric energy, and cooling with water and air and ends with modern refrigeration units operating from the energy of solar radiation and the daily temperature difference of the environment.Result. The peculiarities of making technical decisions underlying the design of the main devices of solar energy refrigeration units are noted. Circuit designs and operating principles of installations and their devices used to improve operating efficiency are described. The main trends in research conducted by scientists to improve the operation of solar energy thermal transformers of cyclic action are considered.Conclusion. This article may be useful to young scientists, engineers and designers for the design and development of innovative autonomous thermal transmitters and refrigeration units for cooling and short-term storage of products and medicines, obtaining food ice, air conditioning, operating independently from solar energy. Such installations are easy to manufacture and operate.